Pengukuran Tingkat Kesiapan Penerapan Sistem INLIS Lite Menggunakan Metode Technology Readiness Index (TRI) - Nesdi Evrilyan Rozanda; Intan Kumala Sari; Idria Maita; Muhammad Luthfi Hamzah4 (STMIK Budi Darma, 2022)
INLIS Lite is a system that functions to assist staff in managing services and users in carrying out activities in the library. INLIS Lite is also an integrated library system developed by National Library of Indonesia as a one-stop software for library managers to implement library automation while developing digital libraries or managing and serving digital collections. The purpose of this research is to measure the readiness of implementing the INLIS Lite system at the UIN SUSKA Riau library. The method used to measure implementation readiness is the Technology Readiness Index (TRI) method. The results of the research that has been done can be concluded that there are 3 variables that influence the level of readiness for implementing the INLIS Lite system, namely the Optimismvariable which has a t-statistic value of 9.961, Innovativeness which has a t-statistic value of 2.544, and Discomfort which has a t-statistic value of 2.260. Insecurity is the only variable that does not affect the level of readiness